Investigation of protective effect of carvacrol in an experimental cataract model - Balbaba, Mehmet; Aslan Mehmetaliogullari, Selma; Ilhan, Nevin; Canleblebici, Mehmet; Ulas, Fatih; Erdag, Murat; Ozdemir, Gokcen (Springer, 2025)
Purpose To investigate the protective effect of carvacrol in an experimental cataract model in rats. Material and methods In this study, twenty-one Sprague Dawley rat pups were randomly assigned to form three groups. Group 1 (control) received a subcutaneous dimethyl sulfoxide (DMSO) solution and served as the control group. Group 2 (selenite) received only subcutaneous sodium selenite (30 nmol/g) and DMSO solution, and, Group 3 (treatment) received subcutaneous sodium selenite and a single intraperitoneal dose of carvacrol (33.3 mg/kg). In all groups, injections were administered as a single dose on postnatal day 10. Cataract formation was evaluated on the 10th day after injection, and cataract grading was made. Morphological examination, quantitative analyses of antioxidant concentrations, oxidative stress markers, Ca2+ ion concentrations, Ca ATPase pump activities and apoptosis-associated proteins in the lenses were evaluated. Results The mean cataract stages in control, selenite and treatment groups were 0.00 +/- 0.00, 3.71 +/- 0.75, and 1.71 +/- 0.48 respectively. There was a statistically difference between the mean cataract stages of control and selenite groups. (p< 0.01) The mean cataract stages of treatment group were significantly reduced compared with selenite group. (p < 0.01) When selenite and treatment groups were compared, in treatment group, antioxidant activity (p < 0.01) and Ca ATPase pump activity (p < 0.01) increased, while oxidative stress markers, Ca(2+)ions concentrations (p < 0.01) and Bax/Bcl-2 ratio (p < 0.05) decreased in the lenses statistically significant. Conclusion The results of the present study suggest that carvacrol administration, owing to its potent antioxidant and anti-apoptotic properties, might attenuate selenite-induced cataractogenesis through multiple mechanisms that are involved in cataract development.
Keywords: Cataract; Carvacrol; Oxidative stress; Apoptosis; Ca2+ ions; Ca ATPase pump